Perkembangan dan Karakterisasi Desa-desa Pegunungan Jawa Tengah: Development and Characterization of Mountain Villages in Central Java - Andi Yoga Saputra; Ernan Rustiadi; Wiwiek Rindayati (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
The characteristics of mountain villages are very different from valley villages and plain villages, but socio-economically and environmentally related to each other. This study aims to analyze the level of development of physical facilities in mountain villages, analyze the village development index based on the dimensions of village development, and analyze the components of socio-economic, environmental, and developmental characteristics of mountainous villages in Central Java. Analysis of the level of development of mountainous village physical facilities used skalogram based on PODES 2018 data, village development index based on the dimensions of village development used the Village Index (ID) calculation formula, and analysis of the characteristics of the socio-economic, environmental, and developmental components of mountain villages used Principal Component Analysis (PCA). Results of the analysis of the level of development of the physical facilities of the mountainous villages show that 413 villages (67.81%) of the mountains are in the third hierarchical class (less developed). The category of village development based on the dimensions of development shows that mountain villages are included in the category of developing villages with an average value of ID 54.17. The components that best characterize the characteristics of mountainous villages are the potential for the danger of 21.9%, the availability of secondary school education facilities, health facilities, and the village development level of 16%, the component of trade facilities 5.8. %, the component of the availability of the micro-industry is 13.25%, and the component of the availability of health facilities are 8.8%.